Research progress on fusion genes in tumours - Yinyi Chang; Zitong Zhao; Yongmei Song (Wiley, 2024)
Abstract Background The concept of gene fusion describes the process of fusing two genes into one, which is closely linked to tumour occurrence and development and may even be the direct cause of some tumours. Due to their tumour‐specific expression and ability to drive tumour occurrence and development, there is great potential for fusion genes to be used as diagnostic markers and targets for specific types of tumours. Main body Although many fusion genes have been detected so far, they mainly focus on a small number of highly recurrent fusion genes detected in patients' tumours. There are few studies on the functional mechanism and clinical relevance of rare gene fusions. Our review discusses the generation mechanisms, detection methods, biological functions, and mechanisms of action of fusion genes. Additionally, we discuss the clinical significance of fusion gene detection in some tumour types. Conclusion The function mechanism research of rare gene fusion is very necessary, and more functions of fusion genes independent of unfused/normal genes can be explored in future studies. There is still a long way to go in implementing precision tumour therapy targeting gene fusion.